Restauração ecológica em áreas reflorestadas no domínio Floresta Estacional Semidecidual - Fragoso, Rosimeri de Oliveira (2013)
This study aimed to evaluate methods of forest restoration in areas reforested in the Corredor de Biodiversidade Santa Maria, located between the cities of Santa Teresinha de Itaipu and São Miguel do Iguaçu-PR, to subsidize projects. The Corredor was established in 2003, however it was identified excerpts containing the invasive species Megathyrsus maximus (Jacq.) B. K. Simon & S. W. L. Jacobs (coloniao grass) and Cyperus rotundus L. (coco grass). The first experiment consisted of evaluate three treatments for forest restoration with planting seedlings, which were: control, green fertilization and soil solarization, in an area with periodic elevation of the groundwater, with discontinuation of reforestation carried out in 2003. The second experiment evaluated an enrichment planting of tree species native to the region, in the area reforested in 2003. The assessments consisted of monthly monitoring of the mortality rate and seedling growth and dry mass obtained from the management of the the invasive species, coloniao grass and coco grass. Furthermore, the changes introduced in the soil at depths of 0-10 cm and 10-20 cm, in three samples of soil during the experiment were evaluated. After over a year of assessment, the first experiment showed no statistically significant differences between treatments on all the variables studied. The mortality was more pronounced in January (12.08%), with smaller percentages for: Enterolobium contortisiliquum (timborí), Schinus terebinthifolius (aroeira), Croton urucurana (sangra-d'água) and Luehea divaricata (açoita-cavalo). About the seedlings development, growth was higher for: Sapium glandulatum (leiteiro-do-banhado), C. urucurana and L. divaricata. Regarding the dry mass of coloniao grass and coco grass in all treatments, the highest values were found in January (94.14 g/m2) and February (132.76 g/m2), remaining low throughout the experimental period. Through soil analyzes, it was observed that treatments showed no significant differences in the results, however, the physical and chemical changes in the soil, were sensitive to coloniao grass and coco grass management. In the second experiment, the mortality reached a percentage of 24.38%, which was more pronounced in the first two months in January (11.88%) and February (5.63%). Regarding the development of seedlings, the species that stood out were Aloysia virgata (Ruiz & Pav.) Juss. (lixeira), and Ceiba speciosa (A.St.-Hil.) Ravenna (paineira). Concerning the dry mass of green panic grass there was not a considerable recurrence over the months, which ranged from 0.04 g to 3.43 g. Through soil analysis, it was possible to observe changes in physical and chemical characteristics analyzed, demonstrating that they were sensitive to soil management in the area, and may also lead to new modifications due development of seedlings